Geographical region and clinical outcomes of patients with primary biliary cholangitis from Western Europe. Issue 1 (17th November 2022) - Murillo Perez, Carla F.; Gerussi, Alessio; Trivedi, Palak J.; Corpechot, Christophe; van der Meer, Adriaan J.; Maria Battezzati, Pier; Lindor, Keith D.; Nevens, Frederik; Kowdley, Kris V.; Bruns, Tony; Cazzagon, Nora; Floreani, Annarosa; et al.
Abstract : Background and aims: The are geographic variations in the incidence and prevalence of primary biliary cholangitis (PBC). The aim was to explore whether clinical outcomes of patients within Western Europe differ according to geographical region. Methods: Ursodeoxycholic acid-treated patients from European centers from the Global PBC database diagnosed from 1990 onwards were included. Patients with a time lag > 1 year from diagnosis to start of follow-up were excluded. Differences in baseline characteristics were studied according to North/South and East/West, whereas outcomes (transplant-free survival and decompensation) were studied with center latitude and longitude. Cox regression analyses were adjusted for age, sex, diagnosis year, biochemical markers, and cirrhosis as a time-dependent covariate. Results: One thousand eight hundred seventy-eight patients were included, and there were no geographical differences in age or sex, with a mean age of 54 years and 89% female patients. Those in North Europe were more often of a moderately advanced/advanced Rotterdam biochemical stage (28.4%) compared with South Europe (20.6%). Additionally, they exhibited higher median alkaline phosphatase (2.0 ×ULN vs. 1.4 ×ULN) and transaminases. In multivariable analysis, there was a significant interaction between center latitude and longitude for decompensation ( P < 0.001) and a trend for transplant-free survival, in which the Northwestern area demonstrated an increased risk for poor outcomes as compared to the reference (Paris). Conclusion: We describe geographic variations in outcomes for patients across Europe from specialist centers in the Global PBC Study Group. Further study is important to explore the potential individual, environmental, and healthcare-related factors that may be contributors.